2004
DOI: 10.1111/j.1365-313x.2004.02288.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the CBF2 and ZAT12 transcription factors in configuring the low temperature transcriptome of Arabidopsis

Abstract: Summary The CBF cold response pathway has a prominent role in cold acclimation. The pathway includes action of three transcription factors, CBF1, 2 and 3 (also known as DREB1b, c and a, respectively), that are rapidly induced in response to low temperature followed by expression of the CBF-targeted genes (the CBF regulon) that act in concert to increase plant-freezing tolerance. The results of transcriptome profiling and mutagenesis experiments, however, indicate that additional cold response pathways exist an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
781
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 711 publications
(825 citation statements)
references
References 55 publications
36
781
1
7
Order By: Relevance
“…AtADH1 was reported to be a cold, dehydration, hypoxia, and ABA-inducible gene [52,53]. Regulation of the ADH1 gene in Arabidopsis by AtCBF2 is suggested by experiments, which alter accumulation of CBF2 [54][55][56] and overexpression of CBF2 [57]. Maruyama et al [17] suggested that the specific promoter elements regulated by DREB2 are ACCGAC, GTCGGT and CCGACT, while DREB1A/CBF3 regulated primarily ACCGAC.…”
Section: Gmdreb1a;2mentioning
confidence: 99%
“…AtADH1 was reported to be a cold, dehydration, hypoxia, and ABA-inducible gene [52,53]. Regulation of the ADH1 gene in Arabidopsis by AtCBF2 is suggested by experiments, which alter accumulation of CBF2 [54][55][56] and overexpression of CBF2 [57]. Maruyama et al [17] suggested that the specific promoter elements regulated by DREB2 are ACCGAC, GTCGGT and CCGACT, while DREB1A/CBF3 regulated primarily ACCGAC.…”
Section: Gmdreb1a;2mentioning
confidence: 99%
“…1, four members (including EARLI1) of this group are closely related and form a separate branch in the HyPRP phylogenetic tree (Josè-Estanyol et al 2004). Interestingly, each of the four members, At4g12470, At4g12480 (EARLI1), At4g12490, and At4g12500, is cold responsive (Vogel et al 2005). Biochemical and genetic approaches were used here to further investigate the potential role EARLI1 and perhaps its closely related paralogs play in plant cell protection.…”
Section: Introductionmentioning
confidence: 99%
“…4). Interestingly, it was shown in Arabidopsis that EARLI1, At4g12490, and At4g12500 had the same co-expression profile in response to cold, while At4g12470 belonged to a different class of cold responsive genes (Vogel et al 2005). Thus, it may be that EARLI1, At4g12490, and At4g12500 have a more significant role in protecting plant and yeast cells from freezing damage than At4g12470, which can be tested in future experiments using transgenic plants.…”
mentioning
confidence: 99%
“…AtCBF1 to AtCBF3 TFs bind DRE cis-elements and induce cold-responsive (COR) gene expression (Gilmour et al, 1998;Shinwari et al, 1998;Maruyama et al, 2004;Vogel et al, 2005) and, consequently, improve freezing tolerance (Gilmour et al, 2004). In addition, CBF gene expression is tightly regulated by calcium.…”
mentioning
confidence: 99%